2013
DOI: 10.4049/jimmunol.1201909
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of Complement (C5) and CD14 Markedly Attenuates Inflammation, Thrombogenicity, and Hemodynamic Changes in Porcine Sepsis

Abstract: Complement and the TLR family constitute two important branches of innate immunity. We previously showed attenuating effects on inflammation and thromogenicity by inhibiting the TLR coreceptor CD14 in porcine sepsis. In the present study, we explored the effect of the C5 and leukotriene B4 inhibitor Ornithodoros moubata complement inhibitor (OmCI; also known as coversin) alone and combined with anti-CD14 on the early inflammatory, hemostatic, and hemodynamic responses in porcine Escherichia coli–induced sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 62 publications
3
39
0
Order By: Relevance
“…We previously demonstrated that coversin is a potent C5 inhibitor in pigs as well as in humans, decreasing E. coli-induced cytokine release in whole blood (54). Furthermore, in a porcine model of E. coli-induced sepsis, coversin attenuated central proinflammatory cytokines such as TNF and IL-6 and efficiently reduced thrombogenicity by reducing the expression of tissue factor (29). The present study demonstrates that coversin led to a significant decrease of almost all tested inflammatory markers.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We previously demonstrated that coversin is a potent C5 inhibitor in pigs as well as in humans, decreasing E. coli-induced cytokine release in whole blood (54). Furthermore, in a porcine model of E. coli-induced sepsis, coversin attenuated central proinflammatory cytokines such as TNF and IL-6 and efficiently reduced thrombogenicity by reducing the expression of tissue factor (29). The present study demonstrates that coversin led to a significant decrease of almost all tested inflammatory markers.…”
Section: Discussionsupporting
confidence: 67%
“…In the earlier study using a porcine model of E. coliinduced sepsis, inhibition of C5 and CD14 attenuated inflammation and thrombogenicity and delayed hemodynamic changes (29). In the current study, it is tempting to suggest that the combined inhibition may have had similar effects on thrombogenic and hemodynamic parameters, which may explain the beneficial effect of combined inhibition on survival.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Well aware that mice are not men (19), translation from rodents to humans has its limitations. Pig models of complement inhibitory therapy in sepsis, in particular in combination with anti-CD14 (20)(21)(22), have yielded promising results. They are more relevant to human pathophysiology than rodent models, but the treatment was limited to only 8 h, as the animals were monitored under full anesthesia.…”
Section: Significancementioning
confidence: 99%
“…[54][55][56], and combined inhibition of CD14 and complement has been suggested as an effective therapeutic approach in conditions associated with detrimental activation of the innate immune system (57,58). We recently showed that combined inhibition on CD14, using the original clone Mil2, and the complement inhibitor OmCI, reduces inflammation, hemostatic disturbances and improved hemodynamics in a porcine model of E. coli sepsis (37). These results were obtained despite the adverse effects seen with the original clone Mil2.…”
Section: Discussionmentioning
confidence: 59%